Konsep Diri pada Masa Remaja Akhir dalam Kematangan Karir Siswa - Fitri Nur Rohmah Dewi (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Self-Concept in Late Adolescence in Students' Career Maturity. The purpose of this study is to explore and understand theoretically and philosophically about self-concept in late adolescence in career maturity. This study uses library research research methods (library research). The results of this study are: Career maturity can be overcome if a person in late adolescence can maximize his self-concept, including internal and external factors in it. Internal factors that can influence self-concept are: 1) self-identity, 2) behavioral self, and 3) self-acceptance or judgment (judging self). While external factors that can influence self-concept are: 1) physical self, 2) ethical-normal self (moral-ethical self), 3) personal self (personal self), 4) family self (family self), and 5) social self. Self-concept needs to exist in late adolescence because with the belief that all achievements are determined by effort, skills and abilities, children in late adolescence will try to improve the abilities and skills that are career requirements.Keywords: Self-Concept, Late Maturity, and Late Adolescence